STRATEGI INOVASI PRODUK DAN LAYANAN DALAM MEMPERTAHANKAN KEUNGGULAN KOMPETITIF PADA FASE PENGENALAN: STUDI KASUS SALON KECANTIKAN WINDI AESTHETIC - Windi Anggia Ayu; Nasharuddin Mas; Ana Sopanah Supriyadi (Bajang Institute, 2025)
This study aims to explore the role of product innovation and service innovation in shaping competitive advantage during the introductory phase of a beauty salon business. The introductory phase is a crucial phase in the business life cycle, where differentiation strategies and customer experience creation are crucial for the business's future sustainability. The research method used was a qualitative case study approach. Data were obtained through in-depth interviews with three beauty experts in Malang City and two active customers who had interacted with Windi Aesthetic Beauty Salon services over a period of time. Data were analyzed systematically through open coding, axial coding, and selective coding to identify relationships between categories and build a deeper understanding of the strategies implemented. Furthermore, thematic coding was conducted, both from the business owner's and customer's perspectives. The results show that product innovations such as the use of natural ingredients and aesthetically pleasing packaging are able to attract customers from the outset. Meanwhile, service innovations such as flexible hours, personalized consultations, and empathetic communication enhance comfort and foster perceptions of professionalism. The combination of these two innovations creates a competitive advantage characterized by responsive service, quality results, and customer loyalty from the early stages of operation. This advantage forms a strong differentiated position and has the potential to become the foundation for long-term growth